Age of Individuals Undergoing Cleft Lip and Cleft Palate Surgeries in Nepal - Shankar Man Rai; Kiran Nakarmi; Surendra Basnet; Pramila Shakya; Krishna Nagarkoti; Mangal Ghartimagar; Bishal Karki; Suzita Hirachan (Journal of Nepal Medical Association, 2013)
Introduction: Timely repair of cleft lip and palate maximises the benefits of surgery. Developing countries have large number of adults with unrepaired clefts. The impact of a cleft program can be determined by observing the trends of lower age at surgery. Public Health Concern Trust, Nepal has been providing a comprehensive nationwide cleft service since 1999. This study was conducted to see any change in the age at surgery.